Humoral immune responses to VP4 and its cleavage products VP5* and VP8* in infants vaccinated with rhesus rotavirus. - Padilla-Noriega, L (1992)
The humoral immune response to rhesus rotavirus (RRV) VP4 and its cleavage products VP5* and VP8* was determined in paired serum samples from 44 infants vaccinated with RRV or human rotavirus-RRV reassortants and 5 placebo recipients. Our aim was to try to measure the response to those regions of VP4 most closely related to protection. An enzyme-linked immunosorbent assay (ELISA) was used to measure the immunoglobulin G immune response to baculovirus-expressed full-length RRV VP4, full-length VP8*, and the amino-terminal polypeptide of VP5* called VP5*(1) (amino acids 248 to 474). The two antigenic regions of VP4 selected for study, VP5*(1) and VP8*, have previously been shown to contain most of the cross-reactive and strain-specific neutralization epitopes, respectively, while the remaining carboxy-terminal half of VP5* (amino acids 475 to 776) has not been clearly associated with neutralization. All three recombinant proteins were antigenically conserved, since they reacted with a library of neutralizing monoclonal antibodies directed at VP4. There was a high percentage of seroresponders to VP4 (61%) or to VP8* (52%), but fewer infants seroresponded to VP5*(1) (11%). In addition, infants responding to VP5*(1) had considerably lower titers than to VP4 or VP8*. Immune response to VP4 correlated strongly with the responses detected by the plaque reduction neutralization assay but did not correlate with the responses detected by the ELISA to whole RRV. These data imply that the VP5*(1) region is less immunogenic than the VP8* region of VP4 in infants immunized with RRV or RRV reassortants. The low immunogenicity of VP5* might adversely affect the efficacy of RRV vaccine candidates.